Multi-objective optimal thermal heat sink design using evolutionary method - Mohd. Hanafi, Mohd. Zainolarifin (Penerbit UTM Press, 2015)
Single and multi-objective thermal performance of heat sink are considered using evolutionary optimization method. The main objective is to obtain an optimal heat sink design for solving thermal problem on CPU electronic package. In this case, single and multi-objective particle swarm optimization are explored for searching the optimal dimensions of plate fin heat sink design. The optimal design could maximize the heat dissipation and minimize the size of heat sink. Based on the previous research finding and preliminary simulation results, thickness and length of plate fin are selected for optimization. Analysis has been conducted to obtain the best convergence rate of iteration process and optimum values of the fitness functions. This study has demonstrated the usefulness of optimization engine in order to obtain the optimal design of heat sink with area reduction is about 27.15% and heat dissipation has increased by 79.33%.